Identifikasi Karakteristik Kawasan Informal Pesisir Kota Bandar Lampung dan Kerentanan terhadap Dampak Perubahan Iklim (Studi Kasus : Kelurahan Kota Karang dan Kangkung) - Ilmi, Warid Zul; Asbi, Adnin Musadri; Syam, Tamaluddin (Universitas Diponegoro, Indonesia, 2021)
This research aims to identify the characteristics of informal areas in Kelurahan Kota Karang and Kelurahan Kangkung and their vulnerability to the impacts of climate change. Climate change is a high-risk threat in the future, events such as flash floods, tidal flooding and water crisis will continue to worsen in coastal areas, and informal communities as a vulnerable group will be greatly affected by this. The method of data collection in this study uses the independent interview method, literature review and observation. The data analysis method used is descriptive qualitative analysis. According to the results of the analysis, the region has endeavored to deal with various shocks and pressures, and has characteristics of resilience as a capital of resilience in facing the impacts of climate change. However, they have not been able to solve all the existing problems.